2018
DOI: 10.1186/s12933-018-0703-2
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes, cardiovascular disease and the microcirculation

Abstract: Cardiovascular disease (CVD) is the leading cause of mortality in people with type 2 diabetes mellitus (T2DM), yet a significant proportion of the disease burden cannot be accounted for by conventional cardiovascular risk factors. Hypertension occurs in majority of people with T2DM, which is substantially more frequent than would be anticipated based on general population samples. The impact of hypertension is considerably higher in people with diabetes than it is in the general population, suggesting either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
272
1
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(303 citation statements)
references
References 99 publications
(111 reference statements)
10
272
1
20
Order By: Relevance
“…Firstly, the stronger association seen in cardiometabolic patients compared with the general population could suggest a synergistic effect on the variation of small and large vessels, where degradation is escalated once the disease begins. This is consistent with other studies showing that individuals with both type 2 diabetes and hypertension have an increased risk of CVD compared with those with either condition alone . Thus, it highlights the potential importance of the microcirculation in CVD pathogenesis and management, which has largely been overlooked.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Firstly, the stronger association seen in cardiometabolic patients compared with the general population could suggest a synergistic effect on the variation of small and large vessels, where degradation is escalated once the disease begins. This is consistent with other studies showing that individuals with both type 2 diabetes and hypertension have an increased risk of CVD compared with those with either condition alone . Thus, it highlights the potential importance of the microcirculation in CVD pathogenesis and management, which has largely been overlooked.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other studies showing that individuals with both type 2 diabetes and hypertension have an increased risk of CVD compared with those with either condition alone. 62 Thus, it highlights the potential importance of the microcirculation in CVD pathogenesis and management, which has largely been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore of utmost importance to extend knowledge of the cellular and molecular mechanisms underlying vascular aging in order to design more effective diagnostic tools, prevention strategies, and therapies to promote healthier aging. The investigation of vascular aging in humans is challenging due to the difficulty of organizing long follow-up longitudinal studies in large population cohorts, as well as inherent complexity of post-analysis due to the concurrence with aging of other confounding cardiovascular risk factors, such as hypercholesterolemia, diabetes, hypertension, and obesity [2][3][4]. These limitations can be circumvented by studying premature aging syndromes characterized by accelerated CVD but lacking other confounding risk factors [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of death worldwide, in part due to progressive aging, the main CVD risk factor [1]. A number of additional factors have been identified that increase the risk of developing CVD, either acting alone or in combination (e.g., hypercholesterolemia, diabetes, sedentary lifestyle, and smoking) [2][3][4]. However, studies on the effects of age alone (the only factor we cannot modify or treat) remain scarce due to their high research costs associated with the necessary long-term resource investment and delays in collecting results.…”
Section: Introductionmentioning
confidence: 99%
“…Several plausible pathophysiological mechanisms may underlie the association of impaired glycemic control and development of HTN; Elevated FPG has been previously associated with arterial stiffness [21][22][23], most likely via oxidative stress and accumulation of glycation end products, and alterations in activities of vasoactive substances [24][25][26]. Furthermore, in patients with DM, the integrity of the vascular wall is more susceptible to damage, specifically in the presence of CV risk factor and these macrovascular changes are also evident in the prediabetic phase [27,28]. In addition to the well-established effects of insulin resistance and hyperglycemia on the macrocirculatory dysfunction, one must not ignore the role of glycemic dysregulation on the microcirculation.…”
Section: Discussionmentioning
confidence: 99%